The Role of Brand Trust and Brand Image on Brand Loyalty on Apple iPhone Smartphone Users in DKI Jakarta - Liowina Adlin Hokky; Innocentius Bernarto (Enrichment : Journal of Management, 2021)
The purpose of this study was to analyze: 1) The positive effect of brand image on brand loyalty, 2) The positive effect of brand trust on brand loyalty, 3) The positive effect of brand image on brand trust, 4) The effect of brand trust in mediating brand image on brand loyalty. Data collection was carried out using questionnaire which was distributed online via Google Form. The target population of this study is Apple iPhone smartphone users in DKI Jakarta, at least 18 years of age, and had purchased the product twice. The number of samples was determined to be 200 samples. The sampling technique used was purposive sampling. Data analysis was performed using Partial Least Square-Structural Equation Modeling (PLS-SEM) approach using Smart PLS software. The result showed that brand image had a positive effect on brand loyalty. In addition, brand trust also had a positive effect on brand loyalty. Furthermore, brand image had a positive effect on brand trust. Lastly, brand trust mediates the effect of brand image on brand loyalty.